Did the Early Byzantine tectonic paroxysm affect also the Adriatic area? - Evelpidou, N.; Pirazzoli, P. (Geomorphology, 2017)
The paper starts recalling the various stages that lead to the definition of the Early Byzantine Tectonic Paroxysm (EBTP), which was determined mainly from fossil uplifted shorelines of the Eastern Mediterranean between the middle of the 4th century and the middle of the 6th century CE. A comparison of catalogues of earthquakes may show that possibly an important event occurred in 361 CE in the northern Adriatic, i.e. near the beginning of a sequence of clustered earth movements. This event is proposed as the most likely for the coseismic subsidence of a known slightly submerged tidal notch that developed along over 200 km of the Croatian shoreline.